Penal populism and public opinion : lessons from five countries - Roberts, Julian V. (Studies in crime and public policy., 2003)
Although criminal justice systems vary greatly around the world, onetheme has emerged in all western jurisdictions in recent years: a risein both the rhetoric and practice of severe punishment at a time whenpublic opinion has played a pivotal role in sentencing policy andreforms. Despite the differences among jurisdictions, startlingcommonalities exist among the five countries-the U.K., USA, Canada, Australia, and New Zealand--surveyed here. Drawing on the results ofrepresentative o.